Studi Eksperimen Kinerja Penukar Kalor Kompak Sebagai Pemanas Tambahan di Rumah Pengering Hibrid - Ludji, Sherly Satriani; Dwinanto, Matheus M.; Koehuan, Verdy A. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
The process of drying a hybrid system that uses a combination of solar energy and biomass contains some useful heat in the chimney of the biomass stove. This heat waste has a high enough temperature so that with the help of a compact heat exchanger it can be used as an additional heater. The purpose of this study was to analyze the performance of a cross-flow type discrete flat plate-finned tube compact heat exchanger with an inline tube arrangement which is used as an additional heating device in the hybrid dryer housing. The test was carried out at 10.00-15.00 for three days of testing with variations in air flow velocity of 1.3 m/s, 1.6 m/s and 1.8 m/s while the velocity of water flow in the pipe was considered constant with 0.000168 m/s. s and the air flow velocity in the exhaust fan is kept constant at 1 m/s. The results of this study indicate that the overall heat transfer coefficient is strongly influenced by the effectiveness of the heat exchanger, and with the increase in the effectiveness of the heat exchanger, the heat transfer coefficient will also increase. The highest overall heat transfer coefficient was obtained on the second day, namely 99.263 W/m2.oC. The total heat transfer rate is influenced by the effectiveness of the heat exchanger but at a certain value both values ​​tend to be stable due to the limited dimensions of the heat exchanger. NTU is very influential on the effectiveness of the exchanger, and in this case the value of NTU ranges from 0.6-0.8 while the effectiveness of the heat exchanger ranges from 46%-56%